Haemoperitoneum Due to Spontaneous Rupture of a Liver Metastasis - Dolapsakis, Christodoulos (Eur J Case Rep Intern Med, 2019)
Spontaneous rupture of a liver metastasis is a life-threatening complication of metastatic liver disease. Although metastatic liver lesions are much more common than primary tumours, spontaneous rupture of a liver metastasis is rare. Therapeutic decisions must take into account the extent of metastatic liver disease and the patient’s performance status. Transarterial embolization may be considered in cases of ongoing haemorrhage despite initial conservative measures. We describe a case of haemoperitoneum due to spontaneous rupture of a liver metastasis in a 72-year-old patient with carcinoma of unknown origin who responded well to conservative management. LEARNING POINTS: Spontaneous rupture of a liver metastasis is a rare but potentially life-threatening complication of metastatic cancer to the liver; risk factors include subcapsular location, rapid tumour growth and tumour necrosis (spontaneous or due to chemotherapy). Unexplained fever often precedes the spontaneous rupture, probably reflecting tumour necrosis or infiltration of the liver capsule, and may raise clinical suspicion for the diagnosis. Transarterial embolization may be considered in cases of ongoing haemorrhage despite initial conservative measures.